Radiofrequency Controlled Ablation Technique for Arthroscopic Meniscectomy of the Knee - Amber Carroll, B.S.; Chris Brice, P.T., D.P.T.; Chaitu Malempati, D.O. (Arthroscopy Techniques)
Despite mixed responses in the literature regarding knee arthroscopies, radiofrequency (RF) ablation remains a preferred method for partial meniscectomy of the knee. This technique is believed to offer advantages over traditional shaving methods, such as reduced risk of long-term fissure propagation and enhanced precision. However, existing literature does not yield a conclusive status of RF’s risk-benefit profile, contributing to a mixed response to its recognized utility and safety in the arthroscopic community. This article details a procedure for performing partial meniscectomy with RF ablation using a feedback-controlled bipolar RF device (WEREWOLF FLOW50 Wand; ArthroCare/Smith & Nephew, Austin, TX), with a focus on parameters that can influence intervention safety. These parameters include device-specific factors such as energy transmission type and field density, as well as surgeon-specific factors such as rest/shutoff time, translation speed, and instrumentation depth. Postoperative care typically involves physical therapy, emphasizing early mobilization and strengthening exercises to ensure optimal recovery. Although our clinic has observed positive results with feedback-controlled bipolar RF for partial meniscectomy, further studies are necessary to conclusively determine the risk-benefit profile of this technique, including long-term follow-up to assess durability and patient satisfaction. Additionally, comparisons with other techniques could provide a more comprehensive understanding of its efficacy and overall impact on patient outcomes.